2014
DOI: 10.1590/s1516-8913201402536
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Design Applied to the Optimization and Partial Characterization of Pectin Liase from a Newly Isolated Penicillium brasilianum

Abstract: Penicillium brasilianum was previously isolated from tea and identified by molecular biology technique. A PlackettBurman design, followed by a complete second order design was used for the screening of most important factors and to maximize the pectin liase (PMGL) activity, respectively. The maximum PMGL activity by P. brasilianum achieved was 9.0 U/mL after 48 h of cultivation in a medium containing pectin (33.0 g/L), yeast extract (30.0 g/L) and potassium phosphate (2.0 g/L) at 30ºC, with a stirring rate of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…To investigate the possible effect of temperature and pH interaction on FFase activities and identify the optimum conditions for both, we performed a set of cultivations according to a CCRD, where the levels of these two independent variables were selected based on the above individually determined optimum values. Such an approach, which is still poorly reported in the literature for biochemical characterization, provides valuable information for a better understanding of how operating variables influence the catalytic process and was already used to investigate the biochemical profile of enzymes of industrial interest such as proteases, cellulases, pectin lyases, and FFase …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the possible effect of temperature and pH interaction on FFase activities and identify the optimum conditions for both, we performed a set of cultivations according to a CCRD, where the levels of these two independent variables were selected based on the above individually determined optimum values. Such an approach, which is still poorly reported in the literature for biochemical characterization, provides valuable information for a better understanding of how operating variables influence the catalytic process and was already used to investigate the biochemical profile of enzymes of industrial interest such as proteases, cellulases, pectin lyases, and FFase …”
Section: Resultsmentioning
confidence: 99%
“…The optimum pH was 6.0 for both activities (Figure 1b), a value coincident with that reported for an A. oryzae FTase. 31 such as proteases, 32 cellulases, 33 pectin lyases, 34 and FFase. 35 From the matrix of independent variables and responses used in CCRD (Table 1), one can see that the highest hydrolytic (159.81-160.63 U mL −1 ) and transfructosylating (63.16 U mL −1 ) activities were obtained in the central points (runs 9 and 10 carried out at 50 C and pH 6.00) and in run 6 (50 C and pH 7.41), respectively, conditions under which the response surfaces showed optimum regions for both ( Figure 2).…”
Section: Effect Of Temperature On Ffase Activities and Stabilitymentioning
confidence: 99%
“…Penicillium is one of the most used genera in biotechnology and Penicillium brasilianum is also a very important biotechnological target for enzyme production as reviewed here [ 15 , 16 , 17 ]. Jørgensen et al [ 15 ] described a series of biotechnological enzymes produced by an isolate of P. brasilianum IBT 20888 isolated from seaweed in Denmark.…”
Section: Penicillium Brasilianum ’ S mentioning
confidence: 99%
“…Zeni et al [ 16 ] reported pectinase-producing microorganisms with polygalacturonase activity including the isolated Penicillium sp. from tea, which was posteriorly identified as Penicillium brasilianum by molecular biology techniques [ 17 ].…”
Section: Penicillium Brasilianum ’ S mentioning
confidence: 99%
See 1 more Smart Citation